Physiological assessment of Olympic windsurfers - Vogiatzis, I.; De Vito, G. (European Journal of Sport Science, 2015)
Olympic boardsailing is a very demanding endurance sport activity. The main reason for this phenomenon is ascribable to the fact that elite windsurfers use pumping for propulsion during sailing. Pumping is a manoeuvre in which the athlete pulls the sail rhythmically so that it acts as a wing, thus providing the board with additional forward motion especially in light and moderate wind conditions. It has been demonstrated, by using portable metabolimeters, that Olympic boardsailing (Mistral board and the current Olympic board the Neil Pryde RS:X) entails high energy and cardiorespiratory requirements. In elite Olympic board-sailors, by measuring energy costs and cardiorespiratory responses, it was found that (in wind velocity conditions ranging between 4 and 15 m s-1) pumping, compared to non-pumping sailing, induced a significant increase in oxygen uptake () and heart rate (HR) demands (from 19.2 to 48.4 ml min-1 kg-1 and from 110 to 165 beats min-1, respectively). In general, across studies the aerobic demand, recorded on various windsurf boards (expressed as% ), was greater than 75%, whilst HR values were greater than 85% of HRmax during actual racing conditions. In conclusion, Olympic class windsurfing can be considered as a high-intensity endurance type of sport that is comparable to other aerobic sporting activities such as rowing. Sail pumping is the crucial factor determining this high intensity of aerobic demand. Moreover, the fact that a typical regatta includes many races over several days implies that particular attention must be paid to the training strategy and the nutritional requirement of this discipline.